Indicators of Health-Related Quality of Life in Cats With Degenerative Joint Disease: Systematic Review and Proposal of a Conceptual Framework - Yeowell, Gillian; Burns, Danielle; Fatoye, Francis; Gebrye, Tadesse; Wright, Andrea; Mwacalimba, Kennedy; Odeyemi, Isaac (Frontiers in Veterinary Science, 2021)
Objectives The assessment of health-related quality of life (HRQoL) is increasingly important in companion animals. There is, however, a paucity of HRQoL research that focusses on cats with degenerative joint disease (DJD). This study describes the development of a conceptual framework to assess HRQoL in cats with DJD/osteoarthritis. Methods The conceptual framework was developed according to published guidelines. A comprehensive search of the CAB Direct, Scopus, PubMed and Web of Science databases was carried out for publications in English from inception to 12 Nov 2019. Search words used were; “cat”; “feline”; “chronic pain”; pain; and “quality of life”. Publications were selected if they were full-text and peer-reviewed, based on primary data and identified or measured behavioral symptoms of chronic musculoskeletal pain in cats. A systematic review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A data extraction form was developed from categories identified in the literature review and piloted on a small number of studies to ascertain the appropriateness for relevant data extraction. Categories were then finalized, and key domains identified. The domains were then synthesized to develop a conceptual framework. Results A total of 454 studies were identified, of which 14 were assessed to be of good quality and included in the meta-synthesis. Seven domains related to HRQoL in cats with DJD were identified from the data: mobility, physical appearance, energy and vitality, temperament, pain expression, sociability and wellbeing. The three main HRQoL domains were: pain expression; mobility, and wellbeing, which impacted all the others. Pain and mobility impacted on all six other domains, with increased pain and decreased mobility negatively impacting physical appearance, energy and vitality, temperament, sociability and wellbeing. Conclusions and relevance This is the first study to develop an evidence-based conceptual framework for the assessment of HRQoL in cats with OA. The conceptual framework suggests that effective management of chronic pain in cats may improve their overall HRQoL.